Evaluation of the in vitro glycemic index of a fiber-rich extruded breakfast cereal produced with organic passion fruit fiber and corn flour - Leoro,Maria Gabriela Vernaza (2010)
The aim of this study was to determine the influence of process parameters and Passion Fruit Fiber (PFF) addition on the Glycemic Index (GI) of an extruded breakfast cereal. A 2³ Central Composite Rotational Design (CCRD) was used, with the following independent variables: raw material moisture content (18-28%), 2nd and 3rd barrel zone temperatures (120-160 ºC), and PFF (0-30%). Raw materials (organic corn flour and organic PFF) were characterized as to their proximate composition, particle size, and in vitro GI. The extrudates were characterized as to their in vitro GI. The Response Surface Methodology (RSM) and Principal Component Analysis (PCA) were used to analyze the results. Corn flour and PFF presented 8.55 and 7.63% protein, 2.61 and 0.60% fat, 0.52 and 6.17% ash, 78.77 and 78.86% carbohydrates (3 and 64% total dietary fiber), respectively. The corn flour particle size distribution was homogeneous, while PFF presented a heterogeneous particle size distribution. Corn flour and PFF presented values of GI of 48 and 45, respectively. When using RSM, no effect of the variables was observed in the GI of the extrudates (average value of 48.41), but PCA showed that the GI tended to be lower when processing at lower temperatures (<128 ºC) and at higher temperatures (>158 ºC). When compared to white bread, the extrudates showed a reduction of the GI of up to 50%, and could be considered an interesting alternative in weight and glycemia control diets.